Białoruś wobec pandemii COVID-19. Praktyka i realia - Fedorowicz, Krzysztof (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2021)
Celem artykułu jest przedstawione podejścia władz Republiki Białoruś wobec pandemii COVID-19. Główna hipoteza badawcza przyjęta przez autora głosi, iż Białoruś od początku pandemii zdecydowała się na świadome ignorowanie pojawiającego się zagrożenia epidemiologicznego, przyjmując strategię uspokajania społeczeństwa i bagatelizowania globalnego niebezpieczeństwa. Na podstawie analizy danych dowiedziono, iż większość Białorusinów podczas pandemii COVID-19 całkowicie utraciło zaufanie do państwa i jego organów, które ich zdaniem okazały się niezdolne do podjęcia ochrony swoich obywateli przed negatywnymi skutkami (zdrowotnymi, ekonomicznymi) pandemii.

The article’s aim is to present the approaches of the authorities of the Republic of Belarus toward the COVID-19 pandemic. The main research hypothesis is that Belarus decided to consciously ignore the emerging epidemiological threat from the beginning of the pandemic by adopting a strategy of appeasing the society and downplaying the global danger. Based on the data analysis, it has been proved that most Belarusians during the COVID-19 pandemic completely lost their trust in the state and its authorities, which in their opinion turned out to be unable to protect their citizens against the negative (health, economic) effects of the pandemic.
Belarus and the COVID-19 Pandemic. Practice and Reality
Keywords: COVID-19; pandemia; Białoruś; protesty; zdrowie; COVID-19; pandemic; Belarus; protests; health